2020
DOI: 10.3390/nu12020345
|View full text |Cite
|
Sign up to set email alerts
|

Inflaming Public Interest: A Qualitative Study of Adult Learners’ Perceptions on Nutrition and Inflammation

Abstract: Research suggests national dietary guidelines are losing public resonance, with consumers actively seeking alternate nutrition advice from unregulated online platforms that often propagate misinformation. Improved diet quality can beneficially affect inflammation, and with science relating to nutrition and inflammation also appealing to consumers, this emerging topic provides an opportunity to consider how novel engagement strategies can be used to increase public support of expert-generated advice. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(22 reference statements)
1
19
0
Order By: Relevance
“…Nutrition professionals need to recognise learning practices and theory, such as connectivism, are evolving with technology. With the general public now having autonomy over their learning and choosing the networks they participate in and who they learn information from, learners need access to evidenced-based nutrition information that is attractive and meets their needs [46]. Nutrition professionals need to regularly engage in a range of networks and communities and tailor messages accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition professionals need to recognise learning practices and theory, such as connectivism, are evolving with technology. With the general public now having autonomy over their learning and choosing the networks they participate in and who they learn information from, learners need access to evidenced-based nutrition information that is attractive and meets their needs [46]. Nutrition professionals need to regularly engage in a range of networks and communities and tailor messages accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Social factors are another aspect that have been highlighted in the MOOCs. Discussion forums in MOOCs find innovative ways to convey safe and accurate information, which allows participants to maintain trust and interaction [14]. Analyzing social interactions has also allowed us to find supporting aspects for terminal efficiency by studying trajectories [15], as well as analyzing the patterns of involvement for MOOCs that are influences on decisions involving pedagogy, depending on the audience to be reached [16].…”
Section: Introductionmentioning
confidence: 99%
“…This may have resonance considering vegetable consumption in Australia where less than 10% of the population achieve recommended vegetable serves [38]. Providing information on more contemporary topics such as nutrition and inflammation also satisfied learner interest [39].…”
Section: Discussionmentioning
confidence: 99%